Analisis Dampak Pasca Pemekaran Kecamatan Serasan Timur Terhadap Kesejahteraan Masyarakat - Panji Al Falah; Nana Amelia Sefti; Aprillia Aprillia; Steviana Br Sihombing; Jupita Natalia; Muhammad Ryandana (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Regional expansion is part of decentralization that aims to improve public welfare through more effective governance. This study analyzes the impact of the expansion of Serasan Timur District, Natuna, on public services, the economy, and infrastructure development. Using a literature study method, this study found that expansion increases the accessibility of administrative services, encourages economic growth through the development of the fisheries, MSMEs, and tourism sectors, and improves infrastructure such as roads, internet networks, education facilities, and health. Although showing positive results, challenges such as human resource management and development sustainability still require attention. This study concludes that expansion is effective in supporting the goals of regional autonomy and recommends strengthening government capacity, economic infrastructure, MSME empowerment, education quality, and health services.